The PENGARUH FLOURISHING DAN EFIKASI DIRI TERHADAP PRODUKTIVITAS KERJA DENGAN KEBAHAGIAAN KERJA SEBAGAI MODERASI - Fransisca Imanuel (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
This study aims to investigate the influence of individual development encompassing positive physical, emotional, psychological, and social aspects (flourishing), as well as individual beliefs in their ability to succeed in performing job tasks (self-efficacy), on work productivity, with work happiness as a moderating variable. Work happiness is measured as the level of satisfaction and happiness individuals feel towards their work. The Structural Equation Modeling method is employed in this research with the assistance of Smart PLS software. The analysis results indicate that both flourishing and work happiness have significant direct impacts on work productivity. Additionally, work happiness moderates the relationship between flourishing and work productivity as well as between self-efficacy and work productivity. These findings suggest that paying attention to and enhancing individual conditions in various positive aspects and increasing work happiness can directly enhance work productivity. Work happiness can also strengthen the relationship between flourishing  and work productivity, as well as between self-efficacy and work productivity, highlighting the importance of psychological and emotional factors in achieving optimal productivity levels in the workplace. These findings provide important contributions for human resources practitioners and organizational management in designing policies and strategies to create a positive work environment, support individual development, boost self-confidence, and promote work happiness as a key factor in enhancing productivity and company performance.